Development of a Solar Power System for Stratospheric Balloon - Teh, Wee Kiat (2016)
Recent advancement in photovoltaic have sparked the integration of solar cells into the development of stratospheric balloon. Contrary to solar cells on Earth, solar cells on stratospheric balloon operate at low temperatures (-60°C to 0°C). This project aims to investigate the performance of solar cells at sub-zero temperatures. Furthermore, to provide insight on the optimal arrangement of the solar array on the stratospheric balloon, solar cell performance was measured by varying the angle of incidence of light. SunPower C60 monocrystalline solar cells connected in series were encapsulated and tested. These cells were exposed to sub-zero temperatures using a commercial freezer and a HPS light source was placed over the solar cell. The electrical parameters were measured using a solar module analyser and efficiency calculated. The encapsulated solar cell was placed on an angular mount at varying angles at room temperature to measure the performance with respect to angle of incidence. It was concluded that Voc and FF decrease while Isc increase with temperature with Voc having a greater dependence with temperature. The efficiency of solar cell decline with increasing temperature. As for angular impact, power output of solar cell increase with decreasing angle of incidence. From these results, the optimal number of solar cells as well as arrangement of solar array could be tabulated. These results would serve as a better platform the planning of solar energy system of a stratospheric balloon.